Imaging cervical cytology with scanning near-field optical microscopy (SNOM) coupled with an IR-FEL - Halliwell, Diane E.; Morais, Camilo L. M.; Lima, Kássio M. G.; Trevisan, Julio; Siggel-King, Michele R. F.; Craig, Tim; Ingham, James; Martin, David S.; Heys, Kelly A.; Kyrgiou, Maria; Mitra, Anita; Paraskevaidis, Evangelos; et al. (Scientific reports, 2016)
Cervical cancer remains a major cause of morbidity and mortality among women, especially in the developing world. Increased synthesis of proteins, lipids and nucleic acids is a pre-condition for the rapid proliferation of cancer cells. We show that scanning near-field optical microscopy, in combination with an infrared free electron laser (SNOM-IR-FEL), is able to distinguish between normal and squamous low-grade and high-grade dyskaryosis and between normal and mixed squamous/glandular pre-invasive and adenocarcinoma cervical lesions, at designated wavelengths associated with DNA, Amide I/II and lipids. These findings evidence the promise of the SNOM-IR-FEL technique in obtaining chemical information relevant to the detection of cervical cell abnormalities and cancer diagnosis at spatial resolutions below the diffraction limit (≥0.2 μm). We compare these results with analyses following attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy; although this latter approach has been demonstrated to detect underlying cervical atypia missed by conventional cytology, it is limited by a spatial resolution of ~3 μm to 30 μm due to the optical diffraction limit.